Productivity of SMEs in the Wood Processing Industry: Case From "Gen Y" in PPU and Kutai Kartanegara, East Kalimantan - Yohanes Kuleh; Erwin Setiawan; Arvita Rachmawaty (Jurnal AGRISEP, 2025)
The urgency of this research is to investigate the partial effects of business length (BL), HR quality (HRQ), and capital (Cpl) on turnover (Tnr), labor costs (LC), market share (MS) to profits (Pft) from active SME clusters operating in wood processing from two East Kalimantan locations, i.e. Penajam Paser Utara (PPU) and Kutai Kartanegara. Data was taken and compiled from interviews with 211 Gen Y as business owners and verified via the panel regression method. In the context of the wood processing industry. This paper finds two main indications. The first model in PPU shows that: (1) BL has a significant impact on Tnr, (2) BR, HRQ, Cpl, and Tnr have a significant impact on LC, (3) BL, HRQ, Cpl, Tnr, and LC have a significant impact on MS, and (4) BL, HRQ, Cpl, and Tnr have a significant impact on Pft. In the second model with the case in Kutai Kartanegara, it proves that: (1) BL and HRQ have a significant effect on Tnr, (2) BL, HRQ, and Cpl have a significant effect on LC, (3) BL, HRQ, Cpl, Tnr, and LC have an effect significant for MS, and (4) BL, HRQ, LC, MS have a significant effect on Pft. The originality of this idea promotes the continuity of SMEs towards a holistic cycle. Practical implications for SMEs in the wood processing industry in both places are able to encourage flexible strategies in business productivity by increasing HR quality, capital, market share and labor costs in a sustainable manner.